Integrated project management - Barkley, Bruce (McGraw-Hill, 2006)
An essential guide for project management professionals, those working toward the PMI PMP certification, and business managers responsible for multiproject programs, Integrated Project Management shows you how to weave PM tools and techniques into the entire fabric of your company and its markets. This landmark book fully addresses the challenge of project integration and thoroughly explains the new PMI PMBOK standard on project integration management. The author explains how to overcome organizational and departmental barriers in order to achieve completely integrated, enterprise-wide PM success and takes you step by step through the integration of PM projects and processes into every area of your company. Filled with detailed cases and applications, Integrated Project Management equips you with: Methods for implementing business plans using PM tools and techniques; a simple conceptual framework for understanding PM integration tools; guidelines for preparing and presenting integrated project proposals to a wide audience of stakeholders and sponsors, and presentation and illustration of the new Project Management Institute Project Management Body of Knowledge (PMBOK) knowledge area on project integration manaagement